Codices Palatini latini - Juristische Handschriften - Huthwelker, Thorsten; Metzger, Wolfgang; Winterer, Christoph (Universität, 2024)
Here you can find the descriptions of the Latin Palatine manuscripts as published in the manuscripts catalog "Die juristischen Handschriften der Codices Palatini Latini in der Vatikanischen Bibliothek (Cod. Pal. lat. 621-813)", edited by Thorsten Huthwelker, Wolfgang Metzger und Christoph Winterer, Heidelberg 2024 (Kataloge der Universitätsbibliothek Heidelberg 13). The description for each manuscript was subsequently recorded as TEI-XML file by XML encoding in accordance with TEI-P5 using GND standard vocabulary. These TEI files follow an outdated TEI schema originally developed at the Herzog August Bibliothek Wolfenbüttel and contain some ad hoc solutions which were chosen pragmatically in Heidelberg and which do not always comply with the TEI Guidelines. A future migration of the dataset into a fully TEI-compliant format is considered as desirable.
Gefördert durch: Deutsche Forschungsgemeinschaft: DFG 251104717
Gesehen am 02.05.2024
Keywords: Forschungsdaten; Datenbank